2019
DOI: 10.1002/hep.30134
|View full text |Cite
|
Sign up to set email alerts
|

CCL15 Recruits Suppressive Monocytes to Facilitate Immune Escape and Disease Progression in Hepatocellular Carcinoma

Abstract: Chemokines play a key role in orchestrating the recruitment and positioning of myeloid cells within tumor microenvironment. However, the tropism regulation and functions of these cells in HCC are not completely understood. Herein, by scrutinizing the expression of all chemokines in HCC cell lines and tissues, we found that CCL15 was the most abundantly expressed chemokine in human HCC. Further analyses showed that CCL15 expression was regulated by genetic, epigenetic and microenvironmental factors, and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 44 publications
3
93
0
Order By: Relevance
“…Above finding prompted us to explore the potential mechanism(s) of PD‐L1 upregulation by CAFs. Prior literature suggests that PD‐L1 upregulated by some cytokines in tumor microenvironment, such as CCL15, IFN‐γ . To determined which cytokines expressed in CAFs were different from normal fibroblasts, qRT‐PCR was performed to scrutinize an amount of six CAFs cells.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Above finding prompted us to explore the potential mechanism(s) of PD‐L1 upregulation by CAFs. Prior literature suggests that PD‐L1 upregulated by some cytokines in tumor microenvironment, such as CCL15, IFN‐γ . To determined which cytokines expressed in CAFs were different from normal fibroblasts, qRT‐PCR was performed to scrutinize an amount of six CAFs cells.…”
Section: Resultsmentioning
confidence: 93%
“…Hence, we speculated that CXCL5 may play a significant role in PD‐L1 expression in melanoma and CRC cells. Notably, other researches showed that serum CXCL5 concentration was significantly higher in nonsmall cell lung cancer patients than those in healthy controls . Those analyses have demonstrated that CXCL5 as a potential biomarker for cancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, two methods are used to construct orthotopic tumor models: injected cancer cells and embedded tumor masses . Considering that the method of using injected cells may cause cells to flow out of the liver capsule, causing experimental errors, we chose to embed tumor masses to construct orthotopic transplantation tumor mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…The body's normal immune system is able to recognize and remove foreign cells or cancerous cells [74]. However, in the inflammatory microenvironment, dynamic changes in inflammation and immune abnormalities develop, which mainly manifest as inflammation-induced immunosuppression and immune escape [75]. Tumor cells also secrete a variety of immunosuppressive factors.…”
Section: Immune Function and Tumorsmentioning
confidence: 99%